(untitled) (Management Strategies and Engineering Sciences, 2027)
The natural gas imbalance crisis in Iran has subjected the country's petrochemical industry, as the most profitable economic pillar and the primary source of non-oil foreign currency earnings, to profound technical and economic challenges. This study takes an applied approach with the aim of developing an economic evaluation model. It models and evaluates the option of importing liquefied natural gas (LNG) through Floating Storage Units (FSUs) at southern ports, distributing it in the ultra-cold liquid phase to destination petrochemical complexes via a virtual pipeline (cryogenic rail and road logistics), and performing decentralized regasification at the destination using Ambient Air Vaporizers (AAVs). The landed cost of LNG ready for overland loading at the Iranian coastal terminal is estimated at approximately USD 13.5 per million British Thermal Units (mmBtu), based on the JKM index and FSU operating tariffs. At the destination, constructing a small-scale regasification facility, comprising AAV vaporizers that require no active energy input along with double-walled strategic storage tanks, adds a cost share of USD 2.0 per mmBtu, bringing the base cost excluding logistics to USD 15.5 per mmBtu. The financial assessment results show that rail logistics, at a variable cost of USD 0.10 per mmBtu per 100 kilometers, is the most efficient transportation method. In the urea producer scenario (intrinsic value of USD 16.52 per mmBtu), the scheme has a definite and profitable economic justification for the Pardis, Shiraz, and Kermanshah petrochemical complexes. In the methanol producer scenario (intrinsic value of USD 12.65 per mmBtu), although the initial direct profit margin is negatively affected by current import prices, the supply of gas during the critical months of the year is evaluated as a fully justified strategic tool for peak shaving when accounting for the opportunity cost of complex survival, the prevention of severe losses from equipment deterioration and catalyst destruction during winter shutdowns, and the potential for optimizing feedstock consumption processes. Furthermore, given that the current imported LNG price of USD 13.5 per mmBtu is high by historical standards, a reduction in geopolitical instability across the Middle East would bring average spot LNG cargo prices in global markets down to the USD 8 to 10 per mmBtu range, rendering methanol producers profitable as well.